Kinerja keuangan daerah terhadap pertumbuhan ekonomi dan pengangguran implikasinya terhadap kemiskinan di kabupaten malinau - Elok Pakaryaningsih (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study was to determine the effect of direct and indirect effect on the financial performance of Regional Economic Growth and Unemployment and poverty in Malinau district. The analysis in this study is using multiple linear regression. The results of the study determines that simultaneous independence ratio, the ratio of effectiveness and efficiency significantly influence the regional economic growth of Malinau district, Partially independent variable is not significant to the effect on economic growth.The variable of effectiveness and efficiency have no influence to the economic growth. The economic growth has no significant effect on unemployment and proverty. The unemployment variable has no significant effect on proverty.